Analisis Program Pembinaan e-Katalog Lokal Bagi Pelaku UMKM di Kota Padang Panjang - Wivi Amelia Rosi; Rahmadhona Fitri Helmi (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
This research is motivated by the existence of MSMEs playing an important role in the economy of a region, including Padang Panjang City. In reality, many MSMEs in this city still have difficulty accessing wider markets and utilizing technology, especially in terms of utilizing local E-Catalogs. This study aims to describe and analyze the implementation of coaching programs for MSMEs regarding the availability of local E-Catalog providers in Padang Panjang City. This research is a qualitative study using descriptive methods. The research was conducted at the Padang Panjang City Regional Secretariat. The informants for this study were determined by purposive sampling. Data were collected through interviews and documentation studies. Data were analyzed by reducing data, presenting data, and drawing conclusions. The results of this study show that communication still needs to be improved regarding the importance of the coaching program. The availability of resources managed has been effective, there is a commitment from the Padang Panjang City Government in organizing the MSMEs coaching program. The implementation of Standard Operating Procedure (SOP) as a technical guide that strengthens the bureaucratic structure in supporting the successful implementation of the MSMEs coaching program as a whole.